PERCEPTION OF MILLENIAL GROUP BUSINESS CONDUCTORS ON HALAL TOURISM IMPLEMENTATION IN LOMBOK ISLAND - Lalu Suparman; Hermanto Hermanto; Aryan Agus Pratama; Baiq Mustika Sari; Baiq Nikmatul Ulya; Lalu Mat'ul Arifin; Uswatun Nafi'ah (Master of Management, Mataram University, 2020)
The tourism industry on the island of Lombok has experienced rapid development and made Halal tourism a leading sector. This study aims to examine the perceptions of tourism business actors from the millennial group in implementing the concept of Halal tourism on the island of Lombok. This study uses a qualitative descriptive phenomenology approach. The data were obtained through observation and in-depth interviews from Muslim tourism businesses which were determined by snowball sampling. The results show that millennial business actors in the tourism sector have good perceptions and positive attitudes towards the implementation of the Halal tourism concept on the island of Lombok. Limited knowledge and understanding regarding Halal indicators and standards is not a big obstacle to applying Halal principles because it is the culture and culture of the people of Lombok.Keywords:Halal Tourism Implementation, Perception, Muslim Millennial Groups, Lombok